A Virtualized Tier-3g Facility Installation for WLCG Network of CERN. (April 2020) - Saygın, H.; Kuday, S.; Alici, A.; Turk Cakir, I.
Abstract: A Tier-3g Facility within the computing resources of Istanbul Aydin University has been planned and installed with the TR-ULAKBIM national Tier-2 center. The facility is intended to provide an upgraded data analysis infrastructure to CERN researchers who are the members in the recent nation-wide projects and international projects such as ATLAS and CMS experiments. The fundamental design of Tier-3g has been detailed in this work with an emphasis on technical implementations of the following parts: Virtualization of all nodes, VOMS usage for reaching fast experimental data in the WLCG network, batch cluster / multicore computing with HTCONDOR and PROOF systems, usage of grid proxies to access code libraries in AFS and CVMFS, dynamic disk space allocation and remote system mounting of EOS. We also present the interpretation of test results that was obtained by the simulation of typical analysis codes.